"Do General", de Onassandro: tradução e estudo - Luiza Monteiro de Castro Silva Dutra (2010)
This work presents the first portuguese translation of Stratgikós, a military manual written by Onasander in the first century A.D. It also investigates the ancient tradition of de re militari treatises through an analysis of their contents and language. In addition, it tries to understand the ideal generals picture according to Onasander by means of comparing it to the other ancient greek and roman authors perspectives on the subject.